Sub-chronic toxicological evaluation of the Baccaurea angulata (Belimbing Dayak) fruit juice in rats - Ibrahim, D.; Hazali, Norazlanshah; Jauhari, N.; Yahya, Mohammad Nor Adros; Ahmed, I. A.; Mikail, Maryam Abimbola; Ibrahim, Muhammad (Healthy-Synergies Publications (USA), 2013)
Summary. Toxicity study on normal rats was carried out using freeze-dried whole fruit (FDWF) sample of Baccaurea angulata. Animals in these sub-chronic studies illustrated no significant changes in general behaviour, growth, and relative organ weights. In liver function test, total protein and alkaline phosphatase significantly decreased in male treated Group-II (300 mg/kg), giving 36.50±2.65 g/L and 47.90±4.48 U/L, respectively. Meanwhile, low dose female group (Group-II), there was significant increase in the same parameters, giving 63.70±5.28 g/L and 73.50±12.91 U/L respectively. In general, there was no evidence that demonstrated any tissue injury, the no-observable adverse effect level for B. angulata was 1,200 mg/kg administered orally for 13 weeks.